Identification and analysis of BAHD superfamily related to malonyl ginsenoside biosynthesis in Panax ginseng - Wang, Ping; Yan, Yan; Yan, Min; Piao, Xiangmin; Wang, Yingping; Lei, Xiujuan; Yang, He; Zhang, Nanqi; Li, Wanying; Di, Peng; Yang, Limin (Frontiers in Plant Science, 2023)
The BAHD (benzylalcohol O-acetyl transferase, anthocyanin O-hydroxycinnamoyl transferase, N-hydroxycinnamoyl anthranilate benzoyl transferase and deacetylvindoline 4-O-acetyltransferase), has various biological functions in plants, including catalyzing the biosynthesis of terpenes, phenolics and esters, participating in plant stress response, affecting cell stability, and regulating fruit quality. So far, the BAHD family has been identified and functionally analyzed in many plants. However, the BAHD gene family has not been systematically identified in Panax ginseng. In this study, 103 BAHD genes were identified in ginseng, mainly distributed in three major clades. Most PgBAHDs contain cisacting elements associated with abiotic stress response and plant hormone response. Among the 103 genes, 68 PgBAHDs are WGD (whole-genome duplication) genes. The importance of malonylation in biosynthesis has led to great attention to the study of malonyltransferases. The phylogenetic tree results showed 34 PgBAHDs clustered with genes that have malonyl characterization. Among them, eight PgBAHDs (PgBAHD4, 19, 36, 39, 45, 65, 97, and 99) showed correlations > 0.9 with crucial enzyme genes involved in ginsenoside biosynthesis and > 0.7 with malonyl ginsenosides. These eight genes were considered potential candidates involved in the biosynthesis of malonyl ginsenosides. This study lays the foundation for further investigation of the mechanism of BAHD genes in ginsenoside biosynthesis.